L-DBF Elicits Cross Protection Against Different Serotypes of Shigella spp - Lu, Ti; Das, Sayan; Howlader, Debaki R.; Zheng, Qi; Ratnakaram, Siva Sai Kumar; Whittier, Sean K.; Picking, William D.; Picking, Wendy L. (Frontiers in Tropical Diseases, 2021)
Shigellosis is a severe diarrheal disease caused by members of the genus Shigella, with at least 80 million cases and 700,000 deaths annually around the world. The type III secretion system (T3SS) is the primary virulence factor used by the shigellae, and we have previously demonstrated that vaccination with the type T3SS proteins IpaB and IpaD, along with an IpaD/IpaB fusion protein (DBF), protects mice from Shigella infection in a lethal pulmonary model. To simplify the formulation and development of the DBF Shigella vaccine, we have genetically fused LTA1, the active subunit of heat-labile toxin from enterotoxigenic E. coli, with DBF to produce the self-adjuvanting antigen L-DBF. Here we immunized mice with L-DBF via the intranasal, intramuscular, and intradermal routes and challenged them with a lethal dose of S. flexneri 2a. While none of the mice vaccinated intramuscularly or intradermally were protected, mice vaccinated with L-DBF intranasally were protected from lethal challenges with S. flexneri 2a, S. flexneri 1b, S. flexneri 3a, S. flexneri 6, and S. sonnei. Intranasal L-DBF induced both B cell and T cell responses that correlated with protection against Shigella infection. Our results suggest that L-DBF is a candidate for developing an effective serotype-independent vaccine against Shigella spp.